Digital Dentistry and Oncology: A Revolutionary Era - Garg, Nisha; Singh Phukela, Sumit; Srivastava, Akansha; Yadav, Jaiveer; Yash, Yash; Kothe, Ananya (Journal of Neonatal Surgery, 2025)
Over the past years the use of technology had a great impact on many fields. There are ongoing development which has colossal effect on field of dentistry. New advances in the field of dentistry has taken over many procedures. Advancements has changed all the aspects of dentistry even altered the flow of traditional treatment processes. Workflow between the different parties involved (dentists, surgeons and dental laboratories) has been affected drastically. The fully digital workflow consists of a direct digitization of the oral cavity utilizing intraoral scanning devices. The digitized file is then utilized as a virtual model by a Computer-Aided Designer (CAD) to virtually design the intended reconstruction. The designed file is then manufactured utilizing computer-aided manufacturing (CAM). Advancements also made a significant contribution to Dental diagnosis in capturing of images from equipment such as RVG, CT Scans, MRI, ECO, EMG etc. Digital dentistry and oncology are two distinct yet increasingly interconnected fields, as advancements in digital technology are significantly transforming both areas.